A numerical simulation method for predicting global and local hydroelastic response of a ship based on CFD and FEA coupling. (May 2018) - Takami, Tomoki; Matsui, Sadaoki; Oka, Masayoshi; Iijima, Kazuhiro
Abstract: In this paper, a simulation method for predicting global and local hydroelastic response of a ship which couples CFD and FEA is developed and validated. By comparing the prediction with linear/nonlinear strip method, 3D panel method and towing tank test results under various wave conditions in terms of rigid body motions and slamming impact pressure, the effectiveness of the CFD-FEA coupling method is confirmed. The hydroelastic behavior, so-called the whipping moment, evaluated from the CFD-FEA coupling method is further validated by comparing with nonlinear strip method, 3D panel method and tank test results. Finally, the proposed method is applied to a realistic large container ship structure in severe waves. The structural response of the double bottom structure subjected to global and local bending moments is investigated. Highlights: Numerical method for predicting global and local hydroelastic response is developed. Developed method is validated regarding hydrodynamic and hydroelastic responses. Contribution of local load to double bottom strength is identified clearly.